The Influence of Brand Image and Word of Mouth on The Purchase Decision of Scarlett Whitening Body Care Products Among Female Students of Prof. Dr. Moestopo (Beragama) University, Faculty of Communication Sciences, Class of 2018 - Ode Savira Cahya Devi, Wa; Juli Hartini, Pratama; Martha, Riesthena (International Journal of Social Science, Education, Communication and Economics, 2024)
This research is a quantitative study which aims to examine the effect of brand image and word of mouth with the purchase decision of Scarlett whitening body care products for University students of Prof. Dr. Moestopo (Beragama). The sample in this study amounted to 86 subjects with data collection methods using purposive sampling technique. The measuring instrument used is the purchase decision scale (30 items, α = 0.959), the brand image scale (12 items, α = 0.847), the word-of-mouth scale (19 items, α = 0.919). The results of this study indicate that there is a significant positive influence between brand image and decision to purchase bodycare products for female students of 0.757, and there is a significant positive effect between word of mouth and decision to purchase bodycare products for female students of 0.764. Furthermore, the results of multiple linear regression data analysis using the computer program SPSS (Statical Product and Service Solution) version 22.0 for windows obtained a correlation coefficient of R = 0.812.